Given that f 1 ( x ) = x + 1 x and f n + 1 = f 1 ( f n ( x ) ) for n ≥ 1 , then find f 2 0 1 4 ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that f 1 ( x ) = x + 1 x and f n + 1 ( x ) = f 1 ( f n ( x ) ) , then
f 1 ( x ) f 2 ( x ) f 3 ( x ) = x + 1 x = f 1 ( f 1 ( x ) ) = f 1 ( x + 1 x ) = x + 1 x + 1 x + 1 x = 2 x + 1 x = 2 x + 1 x + 1 2 x + 1 x = 3 x + 1 x
It would appear that f n ( x ) = n x + 1 x . Let us prove the claim is true for n ≥ 1 by proof by induction . The claim is true for n = 1 . Assuming that it is true for n , then
f n + 1 ( x ) = f 1 ( f n ( x ) ) = n x + 1 x + 1 n x + 1 x = ( n + 1 ) x + 1 x
The claim is also true for n + 1 , therefore it is true for all n ≥ 1 . Then f 2 0 1 4 ( x ) = 2 0 1 4 x + 1 x .
Problem Loading...
Note Loading...
Set Loading...